Analysis of denial of service attack on web security systems. Issue 1 (March 2021) - Iswandi Walad, S.; Zarlis, Muhammad; Syahril Efendi, M.IT
Abstract: In this study, an analysis of the Web security system from a Denial-of-Service Attack (DoS) with SYN Attack, Ping of Death, Land Attack, Smurf Attack and UDP Flood types. The server computer that will be tested for DoS attacks is a local web server including humpuss.com IP: 54.169.71.56, horasindo.com IP: 104.152.168.14, kinarsih.com IP: 156.67.210.132, padanglws.co.id IP: 202.162. 207, 101 and arianaas.com with IP Address 213.136.83.52 port 80. The attack on the local web server computer was carried out through attacking cloned computers as many as 5 zombie computers and then observing data traffic on each Web server computer. The test results use ping to the local web server computer, where the target web server sends a replay request time out and the check results in the Google Chrome browser are slow to inaccessible conditions. Ping access time the greater the packet, the greater the average time when accessing a local web server with 5, 000 packets is 242.68 seconds, 10, 000 packets is 310.28 seconds, 20, 000 packets are 337.4 seconds, 30, 000 packets are 377.2 seconds, 40, 000 packets are 398.4 seconds, 50, 000 packets are 545.4 seconds and 100, 000 packets are above 600 seconds with the condition that the web server will recover after 600 seconds where the system recovery process depends on each local web server.